Effectiveness of an internet‐based intervention to improve sleep difficulties in a culturally diverse sample of international students: A randomised controlled pilot study. (22nd September 2021) - Spanhel, Kerstin; Burdach, Daniela; Pfeiffer, Teresa; Lehr, Dirk; Spiegelhalder, Kai; Ebert, David D.; Baumeister, Harald; Bengel, Juergen; Sander, Lasse B.
Summary: Sleep difficulties are widespread among international students. Internet‐based interventions are suggested as a low‐threshold treatment option but may require cultural adaptation among culturally diverse populations. The present pilot study investigated the effectiveness and acceptance of an internet‐based intervention to improve sleep difficulties in international students. A total of 81 international students of 36 nationalities were randomly assigned to the intervention ( n = 41) or waitlist control group ( n = 40). The intervention group received immediate access to a culturally non‐adapted unguided internet‐based sleep intervention consisting of three modules based on sleep hygiene and cognitive techniques to reduce rumination. At baseline, 4 and 12 weeks after randomisation, insomnia severity, measured by the Insomnia Severity Index, and secondary outcomes (sleep quality, depression, anxiety, perceived stress, well‐being, presenteeism, mental health literacy) were assessed. Data were analysed using linear multi‐level analyses. Additionally, satisfaction and perceived cultural appropriateness of the intervention were evaluated by international students after 4 weeks, and compared with ratings of German students, who represent the original target group. Insomnia severity improved over time in the intervention group compared to the control group, revealing a significant estimated mean difference of −5.60 (Hedges' g = 0.84, p < 0.001) after 12 weeks. Satisfaction and perceived cultural appropriateness was high and comparable to that of German students. The present study shows that a culturally non‐adapted internet‐based sleep intervention can be a low‐threshold treatment option to help meet the high demand for mental healthcare among international students. It thus indicates that cultural adaptation might not represent a precondition for providing effective internet‐based sleep interventions to this target group.